2008
DOI: 10.1016/j.jconrel.2008.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Surface coating of PLGA microparticles with protamine enhances their immunological performance through facilitated phagocytosis

Abstract: Surface modifications of poly(lactide-co-glycolide) microparticles with different polycationic electrolytes have mainly been studied for conjugation to antigens and/or adjuvants. However, the in vivo immunological effects of using surface charged particles have not been address yet. In this study, microparticles were coated or not with protamine, a cationic and arginine-rich electrolyte that confers microparticles with a positively surface charge. We then evaluated the potential of protamine-coatings to assist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 47 publications
(23 reference statements)
3
23
0
Order By: Relevance
“…SEM images of these particles (Figure 1) show smooth surface morphology and confirm the size obtained from volume impedance measurements. The size distribution observed in the SEM images is characteristic of the microparticle synthesis procedure described above, and has been reported elsewhere [9, 23, 24]. Further, the zeta potential of these rapaMPs was determined to be -35.38 ± 4.49 mV (n=4 particle sets).…”
Section: Resultssupporting
confidence: 67%
“…SEM images of these particles (Figure 1) show smooth surface morphology and confirm the size obtained from volume impedance measurements. The size distribution observed in the SEM images is characteristic of the microparticle synthesis procedure described above, and has been reported elsewhere [9, 23, 24]. Further, the zeta potential of these rapaMPs was determined to be -35.38 ± 4.49 mV (n=4 particle sets).…”
Section: Resultssupporting
confidence: 67%
“…The polymer type, the surface decoration of the particles, as well as further excipients and adjuvants all represent factors that enable the modulation of the immunological properties of a particle-based Ag delivery system (35,(46)(47)(48)(49)(50)(51)(52). In studies in which PLGA microparticles were shown to stimulate APCs associated with the release of Ags into the cytosol as consequence of destabilization of the endosomal membrane (53)(54)(55).…”
Section: Discussionmentioning
confidence: 99%
“…37 Furthermore, coating PLGA MPs with protamine, an arginine-rich peptide with strong basic charge, resulted in increased antibodies and T-cell responses in mice. 116 In addition, cellular evidence for enhanced cross-presentation of exogenous antigens encapsulated in protamine-coated PLGA NPs through facilitated antigen uptake and lysosomal escape was provided. These results suggest that protamine-modified PLGA NPs maybe used as a potent adjuvant for cellular vaccines.…”
Section: Cationic Agentsmentioning
confidence: 99%